Mean Platelet Volume-to-Platelet Count Ratio (MPR) in Acute Exacerbations of Idiopathic Pulmonary Fibrosis: A Novel Biomarker for ICU Mortality - Maside Ari; Berna Akinci Ozyurek; Murat Yildiz; Tarkan Ozdemir; Derya Hosgun; Tugce Sahin Ozdemirel; Kerem Ensarioglu; Mahmut Hamdi Erdogdu; Guler Eraslan Doganay; Melek Doganci; Oral Mentes; Omer Faruk Tuten; et al. (Medicina)
Background and Objectives: Acute exacerbation of idiopathic pulmonary fibrosis (IPF-AE) often results in severe respiratory distress requiring treatment in the intensive care unit and has a high mortality rate. Identifying prognostic markers and assessing disease severity are crucial for clinicians to gain detailed insights. The mean platelet volume-to-platelet count ratio (MPR) is an inflammatory marker commonly used in malignancies. This study aimed to evaluate MPR and other factors affecting mortality in patients with IPF-AE who were monitored in the intensive care unit (ICU). Materials and Methods: This retrospective study was conducted on patients monitored in the ICU for IPF-AE between 2017 and 2023. Demographic characteristics, vital signs, laboratory and imaging findings, and administered treatments were reviewed. MPR was calculated by dividing the mean platelet volume by the platelet count. The primary endpoint was defined as 1-month in-hospital mortality. Results: A total of 59 patients monitored in the ICU for IPF-AE were included in the study. The mean age of the patients was 62.75 years, and 81.4% of the participants were male. During the 30-day follow-up period, 62.7% of the patients died. The need for invasive mechanical ventilation (IMV) was significantly associated with increased mortality (p < 0.001). The optimal cutoff value for MPR was determined to be 0.033, with a sensitivity of 83.7% and specificity of 63.64%, indicating its predictive value for mortality (AUC: 0.764; 95% CI: 0.635–0.864; p < 0.001). Conclusions: In this study, the need for IMV emerged as a critical parameter in predicting mortality in patients with IPF-AE. Additionally, the use of the MPR as a prognostic biomarker may offer a novel approach in the management of IPF patients. These findings could contribute to the development of strategies aimed at early intervention in IPF patients. Further studies with larger sample sizes are needed to validate these results. This study has demonstrated that MPR is a significant prognostic biomarker for predicting mortality in patients with IPF-AE who are managed in the intensive care unit. The potential use of MPR as a biomarker in clinical decision-making may provide new approaches to the management of IPF patients. Additionally, the need for IMV in IPF-AE emerges as a critical parameter for predicting mortality. These findings may contribute to the development of early intervention strategies for IPF patients. Further studies with larger cohorts are needed to validate these results.